Determinants of Strategy Implementation in Savings And Credit Cooperative Organizations: A Case Of Tower Sacco in Nyandarua County - Waithira, Mburu Ruth; Kagiri, Asumpta (International Journal of Strategic Management, 2016)
Success of strategy implementation depends on selection of appropriate strategy and converting that strategy into action. Towards this, an entity is required to deal with factors emanation from environment. The objective of this project is to establish the determinants of strategy implementation in SACCOs. To achieve this, researcher used descriptive survey design and targeted 88 respondents of Tower SACCO, used Stratifies Sampling Techniques to obtain representative sample, since the population was not homogeneous. Primary data was collected using self- administered and semi- structured questionnaire and secondary data was taken from background work and literature review of other studies. A copy of data collection questionnaire and instructions was administered by the researcher personally using drop and pick latter method. In Validity, this study used the conventionally acceptable set at 95% to coincide with the 5% convention of statistical significance. Reliability was enhanced through pilot study; test retest method was used. Central editing was done when all questionnaires had been completed and returned, by a single editor who corrected obvious errors. The required statistics was generated with the aid of computer software, Statistical Package for Social Sciences (SPSS) for both descriptive and inferential analysis. The data was organized using descriptive statistics involving percentages, mean scores standard deviation and chi- squire which is presented in frequency distribution tables, charts and graphs. The conclusions of the study were made within the framework of its scope that, resources allocation was the single most determinant of how far the SACCOS implemented the strategy decisions hence by extension the level at which the goals could be realized. Staff involvement and development was the second most determinant of level of strategy implementation. The application of information technology in service delivery was highly ranked as one among the most influencing factor on the level of the strategy implementation hence a key factor for SACCO’s growth and development. Leadership training was among the important factors influencing the level of strategy implementation in Tower SACCO, although it was not statistically significant. Respondents’ demographic characteristics were not statistically significant predicting factors of strategy implementation level.
Keywords: Leaders training; Information technology (IT); Resource allocations; Staff involvement; Strategy implementation